The Influence Of Students' Knowledge And Attitudes As Indicators Of Readiness To Support The Free Nutritious Meal (MBG) Program At Sd Negeri 6 Sawa, North Konawe Regency - Lade Albar Kalza; Ashaeryanto; La Ode Liaumin Azim (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
The Free Nutritious Meal (MBG) program is one of the Indonesian government’s strategic initiatives aimed at improving the nutritional status of school-aged children. The success of this program is influenced not only by food availability but also by students' knowledge and attitudes toward nutrition. This study aims to analyze the influence of students’ nutritional knowledge and attitudes on their readiness to support the MBG program. This research employed a quantitative approach with an explanatory design. Data were collected using questionnaires distributed to students at SD Negeri 6 Sawa, North Konawe Regency. The analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results show that nutritional knowledge has a significant effect on students’ attitudes. Furthermore, students’ attitudes significantly influence readiness to support the MBG program. However, the direct effect of nutritional knowledge on readiness was not statistically significant. These findings indicate that attitude plays an important role in mediating the relationship between knowledge and readiness to support the MBG program. Therefore, nutrition education is essential to strengthen students’ attitudes and support the successful implementation of the MBG program.